The Effects of Artificial Intelligence, Digital Literacy, and Critical Thinking Skills on Students’ Mathematical Problem-Solving Ability - Nurul Resky Amelia; Suradi Tahmir; Fajar Arwadi (Universitas Wiralodra, 2026)
Previous studies have examined the impact of AI use and students’ digital literacy levels. However, they analyzed these variables separately from critical thinking and mathematical problem-solving skills and did not integrate them into a single research model. Therefore, this study integrates these four variables into a single research model to analyze the direct and indirect effects of AI, digital literacy, and critical thinking skills on mathematical problem-solving using a quantitative approach with an explanatory-predictive design in an ex post facto framework. The population in this study consists of all eighth-grade students at public junior high schools in Tamalate Subdistrict, comprising 7 schools with a total population of 1,689 students. The research sample consisted of 11 classes from 4 schools, with a total of 266 students selected through multistage sampling: first, 4 schools were selected using purposive sampling, followed by the selection of classes using proportional cluster random sampling. Data were collected using questionnaires and written tests. All instruments met the criteria for content validity, empirical validity, and reliability. The data were analyzed descriptively and inferentially. Inferential analysis revealed that digital literacy has a direct, positive, and significant effect on critical thinking skills, and that critical thinking skills have a direct, positive, and significant effect on mathematical problem-solving. Conversely, AI has no significant direct or indirect effect on mathematical problem-solving. These findings indicate that critical thinking skills mediate the relationship between digital literacy and students’ mathematical problem-solving abilities, while AI serves as a learning tool that requires digital literacy to support it.